1993
DOI: 10.1111/j.1432-1033.1993.tb18100.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of the reaction catalysed by 2‐aminoethylphosphonate aminotransferase

Abstract: (R)-and (S)-2-amino[2-D,]ethylphosphonic acids ([2-D1]AEP) were synthesised to investigate the stereochemistry of the reaction catalysed by 2-aminoethylphosphonate aminotransferase from Pseudomonas aeruginosa. This enzyme catalyses the transfer of the amino group of AEP to pyruvate to produce 2-phosphonoacetaldehyde and alanine. The enzymic reaction proceeding through the abstraction of a proton from the Schiff-base complex formed between the enzyme-bound pyridoxal 5'-phosphate, and the substrate, was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These experiments showed that R- HAEP is efficiently processed by the enzyme, whereas S -HAEP is completely unreactive. When the reaction between PbfA and R -HAEP was monitored by 1 H NMR, consumption of this aminophosphonate was observed, with the simultaneous appearance of a compound showing the 1 H NMR signature of PAA (t at 9.60 ppm, J = 4.25 Hz; dd at 2.90–2.94 ppm, J = 19.90 and 4.25 Hz) 32 , 33 ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…These experiments showed that R- HAEP is efficiently processed by the enzyme, whereas S -HAEP is completely unreactive. When the reaction between PbfA and R -HAEP was monitored by 1 H NMR, consumption of this aminophosphonate was observed, with the simultaneous appearance of a compound showing the 1 H NMR signature of PAA (t at 9.60 ppm, J = 4.25 Hz; dd at 2.90–2.94 ppm, J = 19.90 and 4.25 Hz) 32 , 33 ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…At present, aminotransferases involved in the anabolism of AEP have not been characterized biochemically, but several enzymes catalyzing the same reaction in organisms that use AEP as a source of nutrients have been studied (29-31). These proteins from Salmonella enterica (31) and Pseudomonas aeruginosa (32) utilize pyridoxal 5′-diphosphate (PLP) as cofactor and pyruvate as ammonium acceptor.…”
Section: -Aminoethylphosphonatementioning
confidence: 99%
“…AEPn is converted to phosphonoacetaldehyde by an AEPnspecific transaminase, and phosphonoacetaldehyde is subsequently converted to acetaldehyde and P i by phosphonoacetaldehyde hydrolase (trivial name, phosphonatase). Enzymes carrying out both of these steps have been characterized for Bacillus cereus (26) and Pseudomonas aeruginosa (12,23). Uptake systems specific for AEPn have also been demonstrated for these bacteria (22,39), consistent with breakdown occurring in the cytoplasm.…”
mentioning
confidence: 97%